Coumarin‐based Chemosensors for Metal Ions Detection. Issue 12 (8th November 2022) - Pooja; Pandey, Harsh; Aggarwal, Sarika; Vats, Monika; Rawat, Varun; Pathak, Seema R.
Abstract: Coumarins, due to their intense and persistent emission of fluorescence, structural flexibility, and excellent biocompatibility, have become a popular choice in developing new fluorescent chemosensors. Coumarins have long been used for sensing anions, cations, chemically reactive nitrogen, oxygen, sulfur‐containing species, and small molecules. They have also been shown to have applicability in imaging, biology, and medical research. Due to the widespread use and excellent biological activity, hundreds of such coumarin motifs have either been isolated from nature or synthesized in a laboratory. This review covers all the developments pertaining to the synthesis and use of coumarin for sensing a variety of metal ions (alkali, alkaline earth, transition, heavy, and noble metal ions). This comprehensive review includes an overview of the coumarin‐based chemosensor's pH limit, detection limit, and binding mode. A brief explanation of the stoichiometric ratio between metal and chemosensor moiety and the applicability of each chemosensor is also given. Abstract : Coumarins, due to their intense emission and excellent biocompatibility, have long been used in imaging, biology, and medical research. Due to their structural flexibility, they have also been used for detecting metal ions, including heavy and noble metals, through the fluorescence‐ON and fluorescence‐OFF phenomenon.